2001
DOI: 10.1007/s11738-001-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

Sulphated flavonoid glycosides from leaves of Atriplex hortensis

Abstract: Two flavonoid sulphates, i.e. quercetin 3-O-sulphate-7-O-aarabinopyranoside and kaempferol 3-O-sulphate-7-O-a-arabinopyranoside, were isolated from leaves ofAtriplex hortensis L. The structures of these compounds were established by UV, 1H and 13C NMR, 2D NMR and MS spectra. The compounds were isolated for the first time from plant material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…The flavonol aglycones: Kaempferol, quercetin, isorhamnetin, sometimes patuletin, spinacetin and tricin were detected in eight Atriplex species (Sanderson et al, 1988). The presence of two new flavonoid sulphates: kaempferol 3-O-sulphate-7-O-arabinopyranoside and quercetin 3-O-sulphate-7-O-arabinopyranoside from leaves of A. hortensis L. was reported by Bylka et al (2001). For A. littoralis, the new acetylated flavonol glycoside was isolated from the aerial part (Bylka, 2004).…”
Section: Phenolic Compounds (Phenolic Acids Flavonoids and Tannins)mentioning
confidence: 95%
“…The flavonol aglycones: Kaempferol, quercetin, isorhamnetin, sometimes patuletin, spinacetin and tricin were detected in eight Atriplex species (Sanderson et al, 1988). The presence of two new flavonoid sulphates: kaempferol 3-O-sulphate-7-O-arabinopyranoside and quercetin 3-O-sulphate-7-O-arabinopyranoside from leaves of A. hortensis L. was reported by Bylka et al (2001). For A. littoralis, the new acetylated flavonol glycoside was isolated from the aerial part (Bylka, 2004).…”
Section: Phenolic Compounds (Phenolic Acids Flavonoids and Tannins)mentioning
confidence: 95%
“…2) of all C. bracteosa extracts in this study were separated, identified and quantified by HPLC-DAD-MS n . 20,21 In such plants, the binding reaction of inorganic sulphates to flavonoids is probably one of the mechanisms connected with the biochemical adaptation of species to their environments. They are found mainly in species occurring in coastal and swampy areas rich in mineral salts, as well as in plants occurring in arid habitats.…”
Section: Phenolic Compounds and Carotenoids From C Bracteosa Extractsmentioning
confidence: 99%
“…In relation to the phenolic compound identification, as seen in Table 1 16,19 Sulphate esters of flavonoids are relatively rare compounds and their functional significance in plant tissues is not clear. 21 Although the phenolic profile of C. bracteosa fruits was reported for the first time in this study, there is another report available, in which two active compounds were identified in the ethyl acetate extracts of C. ulei stems: erythro-2,3-bis(4-hydroxy-3-methoxyphenyl)-3ethoxypropan-1-ol and a known compound, evofolin-B, along with five inactive compounds (betulinic acid, oleanolic acid, pomolic acid, (+)-syringaresinol and ursolic acid). 20,21 In such plants, the binding reaction of inorganic sulphates to flavonoids is probably one of the mechanisms connected with the biochemical adaptation of species to their environments.…”
Section: Phenolic Compounds and Carotenoids From C Bracteosa Extractsmentioning
confidence: 99%
“…The flavonol aglycones: kaempferol, quercetin, isorhamnetin, some times patuletin, spinacetin and tricin were de tected, us ing chro matographic meth ods, in the leaves of eight spe cies from the ge nus Atriplex, ex clud ing A. littoralis L. (Sander son et al 1988). We have pre vi ously re ported the pres ence two new flavonoid sulphates: kaempferol 3-O-sul phate-7-O-arabinopyranoside and quercetin 3-O-sul phate-7-O-arabinopyrano side from leaves of A. hortensis L. (Bylka et al 2001). …”
Section: Introductionmentioning
confidence: 99%